2018
DOI: 10.1029/2018gl078915
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Intraseasonal Variations of the Equatorial Pacific Ocean Between the 1997–1998 and 2015–2016 El Niño Events

Abstract: Oceanic intraseasonal variability (ISV) plays a vital role in the initiation and development of El Niño events. Mooring observations reveal contrasting characteristics of upper-ocean zonal current ISV during different El Niño events. Compared to the 1997-1998 event, ISV of the 2015-2016 event was significantly weaker (by around 30-50%) over the equatorial Pacific basin, and the variability maximum was shifted to the east (~160°E). These differences can be largely explained by wind forcing features. ISV of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Ocean circulation in the western tropical Pacific plays an essential role in the redistribution of heat, freshwater, and biochemical properties over the Indo‐Pacific Oceans (e.g., Fine et al, ; Hu et al, ). Prominent intraseasonal variability (ISV; 20–90 days) in ocean circulation has been detected by in situ observations in this region and reported before (e.g., Azminuddin et al, ; Hu et al, ; Kashino et al, ; Lyu et al, ). One important origin of the upper‐ocean current ISV is the Madden‐Julian oscillation (MJO; Madden & Julian, , ), which is the dominant mode of intraseasonal oscillations of the tropical atmosphere.…”
Section: Introductionsupporting
confidence: 66%
“…Ocean circulation in the western tropical Pacific plays an essential role in the redistribution of heat, freshwater, and biochemical properties over the Indo‐Pacific Oceans (e.g., Fine et al, ; Hu et al, ). Prominent intraseasonal variability (ISV; 20–90 days) in ocean circulation has been detected by in situ observations in this region and reported before (e.g., Azminuddin et al, ; Hu et al, ; Kashino et al, ; Lyu et al, ). One important origin of the upper‐ocean current ISV is the Madden‐Julian oscillation (MJO; Madden & Julian, , ), which is the dominant mode of intraseasonal oscillations of the tropical atmosphere.…”
Section: Introductionsupporting
confidence: 66%
“…Recent studies have indicated that El Niño events show evident diversity and can be broadly classified into eastern Pacific, central Pacific, and mixed type events (e.g., Kao and Yu 2009;Kug et al 2009). Different types of El Niño events have been shown to exert different impacts on the western Pacific circulation (e.g., Hsin and Qiu 2012;Zhao et al 2013;Lyu et al 2018;Tan and Zhou 2018). They have different wind forcing characteristics and possibly affect the MC in different ways.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…From September 2014 to December 2018, a subsurface mooring was deployed at 0°, 142°E to monitor the variability of LEIC. This mooring is a part of the Scientific Observing Network of the Chinese Academy of Sciences in the western Pacific (Lyu et al, 2018; Ma et al, 2019; Song et al, 2018; Wang et al, 2016: Wang, Wang, et al, 2016). The temporal coverage of the mooring data allows the investigation of the interannual variability of LEIC in response to the strong 2015–2016 El Niño event.…”
Section: Introductionmentioning
confidence: 99%